Designing Technology-Supported Collaborative Learning in Vocational Education: An Evidence-Synthesis Framework for SMKN 1 Negeri Besar - Suhendar Fauzi (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2026)
This study reframes the role of educational technology in collaborative learning at SMKN 1 Negeri Besar by replacing an under-specified descriptive design with a structured integrative evidence synthesis and contextual implementation analysis. Eighteen peer-reviewed publications from 2017–2025 were purposively retained from recent literature on computer-supported collaborative learning, digital pedagogy, technical and vocational education and training (TVET), teacher digital competence, and digital equity. School-specific descriptions were treated as contextual documentary evidence rather than participant-level empirical findings. The synthesis shows that technology-supported collaboration is consistently associated with positive learning outcomes, but its effectiveness depends on pedagogical orchestration rather than platform availability alone. Recent meta-analyses report moderate positive effects on academic achievement and collaborative learning, while stronger effects emerge for critical thinking and collaboration skills when digital activities are structured through scripts, feedback, shared accountability, and reflective interaction. In vocational education, five interdependent implementation conditions are identified: equitable access and infrastructure, teacher digital competence, collaborative task architecture, vocational authenticity, and evidence-based feedback and assessment. These conditions are integrated into a contextual framework for SMKN 1 Negeri Besar. The contribution of the study is therefore not a causal estimate of technology effectiveness at a single school, but a theoretically grounded and evidence-informed model for designing collaborative digital learning in resource-sensitive vocational settings.